The best of Josie and the Pussycats - Bennett, Marguerite 1988-; Doyle, Frank 1917-1996; Gladir, George 1925-2013 (Archie Comics, 2017)
"It's time to celebrate the world's most famous fictional band Josie and the Pussycats with this huge, full-color collection of over 400 pages of the most rockin' stories spanning over six decades! Also included are entertaining behind-the-scenes anecdotes about the comics and the influence of Josie and the Pussycats from comic writers, artists, editors and famouns fans!"--Page [4] of cover
"This book contains some material that was originally created in a less socially sensitive time in our society and reflects attitudes that may be interpreted as being unacceptable today. The stories are reprinted here without alteration for historical reference."--Page [3] of book
Keywords: Musikgruppe; Frau; Freundschaft; Comic